2018
DOI: 10.1002/ajmg.b.32702
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of pathogenic variants in genes associated with inborn errors of metabolism in psychiatric populations

Abstract: Many genetic conditions can mimic mental health disorders, with psychiatric symptoms that are difficult to treat with standard psychotropic medications. This study tests the hypothesis that psychiatric populations are enriched for pathogenic variants associated with selected inborn errors of metabolism (IEMs). Using next‐generation sequencing, 2046 psychiatric patients were screened for pathogenic variants in genes associated with four IEMs, Niemann‐Pick disease type C (NPC), Wilson disease (WD), homocystinuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…There are hundreds of IEMs with a collective prevalence estimated to be 50.9 per 100 000 live births (0.051%) and IEMs comprise the largest proportion of genetic disorders that have currently available treatments (Saudubray & Garcia-Cazorla, 2018;Waters et al, 2018). In a previous pilot study (Sriretnakumar, Harripaul, et al, 2019), we showed an enrichment of mutations in genes associated with four treatable IEMs (NPC, homocystinuria due to cystathionine beta-synthase deficiency, Wilson disease, and AIP) in a cohort of SSD, BAD, and MDD patients, with a putative affected rate of 0.34% with these four IEMs. The findings from the current study identified 27 patients (1.17%) putatively affected with an IEM, representing over 23-fold enrichment of treatable IEMs within our psychiatric cohort relative to the collective prevalence of all IEMs.…”
Section: Genementioning
confidence: 99%
“…There are hundreds of IEMs with a collective prevalence estimated to be 50.9 per 100 000 live births (0.051%) and IEMs comprise the largest proportion of genetic disorders that have currently available treatments (Saudubray & Garcia-Cazorla, 2018;Waters et al, 2018). In a previous pilot study (Sriretnakumar, Harripaul, et al, 2019), we showed an enrichment of mutations in genes associated with four treatable IEMs (NPC, homocystinuria due to cystathionine beta-synthase deficiency, Wilson disease, and AIP) in a cohort of SSD, BAD, and MDD patients, with a putative affected rate of 0.34% with these four IEMs. The findings from the current study identified 27 patients (1.17%) putatively affected with an IEM, representing over 23-fold enrichment of treatable IEMs within our psychiatric cohort relative to the collective prevalence of all IEMs.…”
Section: Genementioning
confidence: 99%
“…Apart from common variants that individually contribute minimal disease-risk, another source of genetic risk are rare, highly penetrant and/or deleterious variants 15 . Recent studies of TRS have indicated an increased burden of rare damaging variants in mutation intolerant genes 16,17 and gene sets implicated in Mendelian diseases or specific biochemical pathways, such as neurotransmission and gene targets of antipsychotic drugs [18][19][20] . In CNV analysis, focusing on highly penetrant variants can involve identifying rare but recurrent CNVs impacting loci associated with clinical phenotypes (i.e., disease-associated CNVs).…”
Section: Introductionmentioning
confidence: 99%
“…Another causative gene, NPC2, was identified as HE1 11) . The prevalence of NPC is estimated as 0.14-2.2 per Mass Spectrometry Advance Publication next-generation sequencing has also been employed [27][28][29][30][31] . Many mutations have been reported to date, and novel mutations continue to be characterized 32) .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, next-generation sequencing has also been employed. 27 31 ) Many mutations have been reported to date, and novel mutations continue to be characterized. 32 ) However, a significant disadvantage of these methods is their high running cost.…”
Section: Introductionmentioning
confidence: 99%